Neutrophil extracellular traps in fungal infections: A seesaw battle in hosts - Zhong, Hua; Lu, Ren-Yi; Wang, Yan (Frontiers in Immunology, 2022)
Fungal infections are a growing health care challenge. Neutrophils play a key role in defense against fungal infections. There are many effective ways for neutrophils to eliminate fungal invaders, such as phagocytosis, oxidative bursts, and the formation of extracellular traps. This process has received considerable attention and has made rapid progress since neutrophil extracellular traps (NETs) formation was described. Here, we describe the formation, induction, and function of NETs, as well as fungal strategies against NETs hunting. We highlight the effects of NETs on common fungal pathogens and how these pathogens survive.